Effectiveness of Casirivimab-Imdevimab and Sotrovimab Monoclonal Antibody Treatment among High-Risk Patients with Sars-Cov-2 Infection: A Real-World Experience - Murugapandian, Sangeetha; Gungor, Ahmet B.; Al-Obaidi, Mohanad; Thajudeen, Bijin; Wong, Ryan C; Mansour, Iyad; Zangeneh, Tirdad T.; Johnson, Katherine M.; Low-Adegbija, Nicole E.; Alam, Ruhaniyah; et al. (Archives of Clinical and Biomedical Research, 2023)
Background: Severe acute respiratory syndrome coronavirus 2 (SARSCoV- 2) can evade neutralizing antibodies, raising concerns about the effectiveness of anti-spike monoclonal antibodies (mAb). Methods: This study reports a retrospective data analysis in Banner Health Care System. Out of 109,788 adult patients who tested positive for COVID-19, the study cohort was split into patients who received Casirivimab-Imdevimab (Cas-Imd) (N=10,836; Delta-predominant period 6/2021-11/2021) and Sotrovimab (N=998; Omicron-predominant period 12/2021-1/2022) mAb compared to propensity-matched control groups (N=10,836 and N=998), respectively. Index date was the date of mAb administration or the date of positive COVID-19 testing. The primary and secondary outcomes were the incidence of composite outcome (all-cause hospitalization and/or mortality) and ICU admission at 30-days following index date, respectively. Results: Compared to the propensity-matched untreated control cohort, the Cas-Imd mAb reduced the composite outcome (from 7.5% to 3.7%; difference: -3.8% [95% CI: (-4.4%, -3.2%)], p <0.01) regardless of their vaccination status, while Sotrovimab mAb did not (5.0% vs. 3.8%; difference: -1.2% [95% CI: (-3.1%, 0.7%)], p=0.22). In terms of the secondary outcome, similarly Cas-Imd mAb decreased ICU admission during the first hospitalization (from 1.5% to 0.5%; difference: -1.0% [95% CI: (-1.3%, -0.7%)], p <0.01) compared to the control group, whereas Sotrovimab mAb did not (0.9% vs. 0.6%; difference: -0.3% [95% CI: (-1.2%, 0.6%)], p =0.61). Comparing the periods, the Omicronpredominant period was associated with lower composite outcome than that during the Delta-predominant period. Conclusions: Cas-Imd mAb was effective against the SARS-CoV-2 Delta variant, however sotrovimab lacked efficacy in patients with SARS-CoV-2 Omicron-predominant period.